Clustering in the nucleus of Be8. - Webber, John C. (University of Ottawa (Canada), 1964)
At the present time, the meaning of the cluster model and what is meant by clustering in actual nuclei has not been fully clarified. It is thought that some progress is made here in an understanding of clustering in nuclei. Along with defining the cluster model, the amount of ad hoc involved in the choice of a certain cluster model of a nucleus is given. Also presented here, is a quantitative measure of the amount of clustering occurring in the nucleus. A calculation of this measure of the degree of clustering in the Be 8 nucleus is performed with success. It is demonstrated that Be 8 is slightly ellipsoidal in shape and much less dense than a free alpha particle, The radius of the alpha particles within Be8 is calculated and compared with the radius of a free alpha particle. The separation of the alpha particles is found to be much less than the magnitude of the alpha cluster radius. This investigation also revealed certain new mathematical and physical properties of the cluster model.
Keywords: Physics, Nuclear.